2013
DOI: 10.1080/14786419.2012.725396
|View full text |Cite
|
Sign up to set email alerts
|

A new cytotoxic steroidal saponin from the rhizomes and roots ofSmilax scobinicaulis

Abstract: A phytochemical investigation of the EtOH extract from the rhizomes and roots of Smilax scobinicaulis resulted in the isolation of a new isospirostanol-type steroidal saponin, namely (25 R)-5α-spirostan-3β,6β-diol 3-O-β-D-glucopyranosyl-(1 → 4)-[α-L-arabinopyranosyl-(1 → 6)]-β-D-glucopyranoside (1), along with four known steroidal saponins (2-5). The structures of these compounds were determined by 1D- and 2D-NMR spectroscopic analysis, FABMS and HR-ESI-MS as well as chemical degradation. The isolated saponins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The occurrences of parisyunnanoside in the genus Smilax indicated the close chemtaxonomic relationship between the genus Smilax and Paris . Three isonarthogenin glycosides 24 , 25 , and 28 were isolated from S. scobinicaulis , together with two tigogenin glycosides 38 – 39 [21]. Sieboldogenin ( 33 ), with an additional hydroxyl substitution on C-27 in comparison with laxogenin, was identified from the ethyl acetate fraction of S. china [22].…”
Section: Chemistry Of Steroidal Saponinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrences of parisyunnanoside in the genus Smilax indicated the close chemtaxonomic relationship between the genus Smilax and Paris . Three isonarthogenin glycosides 24 , 25 , and 28 were isolated from S. scobinicaulis , together with two tigogenin glycosides 38 – 39 [21]. Sieboldogenin ( 33 ), with an additional hydroxyl substitution on C-27 in comparison with laxogenin, was identified from the ethyl acetate fraction of S. china [22].…”
Section: Chemistry Of Steroidal Saponinsmentioning
confidence: 99%
“…Compounds 24 , 25 , 28 , 38 , and 39 , were evaluated for the cytotoxicities against three human cancer cell lines (A549, LAC and Hela). Only compound 38 possessed significant cytotoxicities with IC 50 values of 3.70, 5.70 and 3.64 μM, respectively [21]. Another cytotoxic compound is isospirostane glycoside 32 , which displayed potent cytotoxicities against the Hela and SMMC-7221 cancer cell lines with IC 50 values of 9.73 ± 1.64 and 21.54 ± 1.64 μM, respectively [28].…”
Section: Biological Activities Of Steroidal Saponinsmentioning
confidence: 99%
“…The rhizomes and roots of this plant, known as “Jin Gang Teng” and “Wei Ling Xian” in North China, have long been used in folk medicine for the treatment of rheumatic arthritis, lumbago, gout, tumor and inflammatory diseases [1]. Previous phytochemical investigations of this plant led to the isolation of steroidal saponins [4], flavonoids [5] and phenylpropanoids [6]. Bioactivity investigations showed that some of the isolated steroidal saponins had antimicrobial and cytotoxic activity [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical investigations of this plant led to the isolation of steroidal saponins [4], flavonoids [5] and phenylpropanoids [6]. Bioactivity investigations showed that some of the isolated steroidal saponins had antimicrobial and cytotoxic activity [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have isolated compounds that have been used individually or in combination to induce cell death in different cancer type cells. The steroidal saponins(25 R)-5α-spirostan-3β,6β-diol 3-O-β-D-glucopyranosyl-(1-4)-[β-L-arabinopyranosyl-(1-6)]-β-D-glucopyranoside was cytotoxic for A549, HeLa, and LAC human cancer cell lines[49]. The steroidal saponin tupichinin A, together with seven known compounds isolated from rhizomes of Tupistra chinensis Baker, showed potent cytotoxicity against the cancer cell lines HL-60, SMMC-7721, A-549, MCF-7, and SW480[50], while the mixed saponins balanitin-6 and -7 showed anti-tumor activity in both in vivo and in vitro systems[51].…”
mentioning
confidence: 99%